Synthesis Some Heterocyclic Compound based on 2,5–disubsituted Pyridine - Al- Zobaydi, Shatha F N; Hassan, Eman M M (Al-Nahrain Journal of Science, 2013)
The aim of the present study is to determine the useful of Schiff bases derivatives (oxazepine, tetrazole) compounds which used as drug and antimicroble the present work involved preparation starting from 2,5– diaminopyridine a variety of schiff bases and heterocyclic (oxazepine, tetrazole) have been and heterocydic (oxazepine, tetrazole) have been synthesis, all proporsed structure were supported by, FT-IR, 'H-NMR, Elemental analysis, Microbial study.